Konsep Kepelbagaian Budaya Di Dalam Filem - Syukriyah, Binti Sabry. (Universiti Malaysia Sarawak (UNIMAS), 2018)
The research will explore cultural diversity in film which the concept is applied in a self made action and sci-fi short film entitled "The Relation". The researcher applied few elements in the film such as characters from different ethnicity, multiple wardrobe types and mise-en-scene as the core and the main focus of the research.